Benefits of Mixed Reality Simulations in Online Courses - Carver, Lin; Lamb, Jodi (International Journal of Educational Technology and Learning, 2020)
Online learning has become an important component of higher education. Incorporating technology necessitates the consideration of additional factors related to choosing appropriate teaching pedagogy and experiences for knowledge construction. Despite these challenges, it is “often taken for granted that technologies can ‘enhance learning’” (Kirkwood & Price, 2014) based on increased student engagement in online instruction. It is important that faculty learn how to employ enhanced instructional strategies and gain an understanding of why it is so important. This study focuses on gaining an understanding of the perceptions held by students and instructors after the use of a mixed reality simulation. Qualitative data were collected through the use of semi-structure interviews with the instructors and journal reflections from the students. The interview responses and journal entries were analyzed for emerging themes and then axial coding methodology was used to identify the relationships among the themes and frequency. Findings indicate that mixed reality simulations do have a positive impact on students.